African Farmer-led Irrigation Development: re-framing agricultural investments? - Komakech, Hans (2016)
Presented by Dr. Hans Komakech, Nelson Mandela University-AIST, at the workshop on “New Directions for Irrigation Development in Tanzania: The Context of Public Private Partnership”, September 2, 2016.